Foreign Direct Investment Policies in Developing Countries: A Comparative Policy Study - Elinda Novita Dewi; Layyinatus Shifah; Sugianto Sugianto (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study investigates how alternative foreign direct investment (FDI) policy configurations shape developmental outcomes across developing countries using a comparative panel design covering 2005–2022. A composite FDI Policy Regime Index is constructed from coded national policy measures capturing liberalization intensity, performance requirements, incentive structures, screening mechanisms, and green investment provisions. Employing fixed-effects, system Generalized Method of Moments, quantile regression, and panel threshold models, the analysis evaluates impacts on economic growth, structural transformation, and environmental sustainability. The findings indicate that policy configuration matters more than inflow magnitude, with significant heterogeneity across income groups and institutional contexts. Growth and industrial upgrading effects materialize primarily where governance quality and financial development exceed identified thresholds. Environmental outcomes reveal conditional support for the pollution halo hypothesis, as renewable energy adoption increases and carbon intensity declines under credible regulatory and innovation-oriented regimes. The results highlight the importance of institutional complementarities and cross-policy coherence in maximizing developmental gains from FDI, offering evidence-based guidance for sustainable investment policy design in developing economies.